Association of obstructive sleep apnoea with the presence and severity of non‐alcoholic fatty liver disease. A systematic review and meta‐analysis. Issue 5 (6th February 2013) - Musso, G.; Cassader, M.; Olivetti, C.; Rosina, F.; Carbone, G.; Gambino, R.
Summary Obstructive sleep apnoea syndrome (OSAS) and non‐alcoholic fatty liver disease (NAFLD) are common in clinical practice. NAFLD encompasses simple steatosis and non‐alcoholic steatohepatitis (NASH): both confer an increased risk of cardiovascular disease and diabetes; NASH increases also liver‐related risk. Growing experimental evidence connects chronic intermittent hypoxia of OSAS to NAFLD. We reviewed English and non‐English articles and international meeting abstracts through December 2012. Observational studies were included if they assessed OSAS by polysomnography and NAFLD by histological, radiological or biochemical criteria. Two reviewers evaluated retrieved articles by appropriate quality scores. Main outcomes were pooled using random‐ or fixed‐effects models. The effect of age, sex and body mass index (BMI) on effect estimates was assessed by meta‐regression. Eighteen cross‐sectional studies (2, 183 participants) were included. Pooled odds ratios (ORs) of OSAS for the presence of NAFLD, as defined by histology, radiology, and AST or ALT elevation, were 2.01(95% CI: 1.36–2.97), 2.99(1.79–4.99), 2.36(1.46–3.82) and 2.60(1.88–3.61), respectively. Pooled ORs of OSAS for NASH, fibrosis‐any stage, or advanced fibrosis in biopsy‐proven NAFLD patients were 2.37(1.59–3.51), 2.16(1.45–3.20) and 2.30(1.21–4.38). The magnitude and direction of effects were unaffected by age, sex and BMI. In conclusion, OSAS is associated with an increased risk of NAFLD, NASH and fibrosis. OSAS patients should be screened for the presence and severity of NAFLD.